2007
DOI: 10.1200/jco.2006.06.3081
|View full text |Cite
|
Sign up to set email alerts
|

A Cost-Effectiveness Analysis of Adjuvant Trastuzumab Regimens in Early HER2/neu–Positive Breast Cancer

Abstract: AT has an ICER comparable to those for other widely used interventions. Longer clinical follow-up is warranted to evaluate the long-term efficacy and toxicity of different AT regimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 32 publications
3
103
1
2
Order By: Relevance
“…21 More recent studies have concluded that one year of adjuvant Herceptin therapy is a cost-effective treatment for early breast cancer. 22,23 An assessment of the Australian context concluded that given as adjuvant therapy, Herceptin 'may be cost-effective when given over either 52 or 9 weeks at current acquisition costs', 24 also noted that the cost-effectiveness 'with respect to mortality remains uncertain'. 24 Another concern is whether subsidization means that other treatments will be disadvantaged, given limited healthcare budgets.…”
Section: Introductionmentioning
confidence: 99%
“…21 More recent studies have concluded that one year of adjuvant Herceptin therapy is a cost-effective treatment for early breast cancer. 22,23 An assessment of the Australian context concluded that given as adjuvant therapy, Herceptin 'may be cost-effective when given over either 52 or 9 weeks at current acquisition costs', 24 also noted that the cost-effectiveness 'with respect to mortality remains uncertain'. 24 Another concern is whether subsidization means that other treatments will be disadvantaged, given limited healthcare budgets.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the cost of diagnostic testing, significant treatment costs include acquisition costs, administration costs (nursing and pharmacy time), and the costs of clinical cardiac monitoring. Numerous cost-effectiveness studies suggest that costs are comparable to other accepted and standard uses of healthcare dollars [42][43][44][45][46] ; nevertheless, factoring in treatment costs when selecting from among safe and effective treatment options improves the overall cost-benefit ratio of the intervention. Selected treatment costs for chemotrastuzumab sequences and concurrent trastuzumab-taxane regimens are summarized in Table 4.…”
Section: How Do Trastuzumab-based Regimens Compare In Terms Of Cost?mentioning
confidence: 99%
“…Although the response to endocrine therapies is slightly lower for patients with HER-2ϩ tumors, one would still expect that the recurrence risk would be reduced to ϳ10% with adequate hormonal therapy. If we were to extrapolate the benefit of adjuvant trastuzumab with chemotherapy from the large adjuvant trials (Table 1), this risk could be reduced to about 5% with an adjuvant trastuzumab-based chemotherapy regimen, but it would include a risk up to 5% for cardiomyopathy and a cost of as much as $50,000 (trastuzumab) to $100,000 per year (with chemotherapy) [14]. Third, the pros and cons of various adjuvant trastuzumab regimens need to be carefully weighed.…”
Section: By Aditya Bardia Massachusetts General Hospital Cancer Centementioning
confidence: 99%
“…However, the predominantly anthracycline and taxane chemotherapy backbone used in the adjuvant trials may not be necessary for all patients, in particular those with tumors Ͻ1 cm or with negative lymph nodes. Trials evaluating trastuzumab in combination with single-agent taxanes [13] or docetaxel and cyclophosphamide [14], for example, may provide alternative treatment strategies for this subgroup of patients. In addition, whether or not some women may gain the most benefit from an adjuvant approach that uses anti-HER-2 therapy alone is of great interest, and clinical trials are currently being designed to evaluate this question.…”
Section: By Aditya Bardia Massachusetts General Hospital Cancer Centementioning
confidence: 99%